A Study of Chemical Processes of Nitrate in Atmospheric Aerosol and Snow Based on Stable Isotopes - Mengxue Chen; Hewen Niu; Yankun Xiang (Atmosphere, 2023)
Nitrate (NO3−) is a prominent atmospheric pollutant and a key chemical constituent of snow and ice, which plays a crucial role in the atmosphere and significantly impacts regional climate and environment conditions through a series of complex chemical processes. By summarizing the recent research progress on the nitrate chemical process (particularly on the isotopic measurements of NO3− (δ15N, Δ17O and δ18O)) in atmosphere and glacier snow, this study mainly investigated the chemical compositions and chemical processes, formation pathways, and photochemical reactions of nitrate in snow and atmosphere. Our results identified that the main ways of atmospheric nitrate formation are the hydrolysis of N2O5 and the reaction of ·OH with NO2; the spatial distribution of Δ17O and δ18O values of atmospheric nitrate have a significant latitudinal trend between 30° N–60° N; the study of stable isotopes (δ15N and δ18O) and the oxygen isotope anomaly (Δ17O) of nitrate have mainly been carried out over the densely populated and coastal mega cities; there exist significant gaps in the study of chemistry processes of nitrate in snow and ice and the air–snow interfaces across glaciated regions. This study provides a basic reference for more robust observations and research of nitrate in glacier areas in the future.